KAPASITAS LENTUR BALOK BETON BERTULANG PERKUATAN CARBON FIBER WRAPS (CFW) (BALOK DIBEBANI OLEH BEBERAPA KONDISI PEMBEBANAN AWAL DAN KEMUDIAN DIPERKUAT DENGAN CFW) - , ALBERT AUN UMBU NDAY, Prof. Ir. Hrc. Priyosulistyo, M.sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
At this moment the use of reinforced concrete in buildings is familiar. In the development of performance evaluation in the field of structures needs special attentions such as strengthening of buildings. Evaluation of quality starts from manufacturing concrete process until concrete hardening. The purpose of this research is to know the ultimate flexural strength by carbon fiber wraps (CFW) strengthening on the reinforced concrete beam that has already been initially loaded under variable presumed self weight. This research used 4 beam specimens consists of : 1 control beam (BK), 1 reinforced beam with CFW with no initial load (BP 0%), and two reinforced beams after being loaded of 30% and 60% ultimate load (BP 30% and BP 60%). Beams are 150 mm wide, 200 mm high, and 2000 mm long. Beam with simple support on both ends are loaded at the center span. Parameters measured in this research are load, deflection, steel strain, and crack pattern. Test results are compared to the theoretical analysis in accordance with PT. Sika Nusa Pratama formulae (Seminar : The Latest Sika Technology in Structural Strengthening with â SIKA CARBODURâ Composite Strengthening System). From the test results it can be concluded that the strength of BP 0%, BP 30%, and BP 60% are respectively 114.28%